Camera‐assisted nursing observation of restless patients in an acute care setting, a multi‐method feasibility study - Mette Geil Kollerup; Gitte Tolstrup; Birgitte Schantz Laursen (Wiley, 2022)
Abstract Aim To evaluate the implementation, practicality and acceptability of camera‐assisted observation of restless patients in the acute care ward. Design A multi‐method feasibility study. Methods Data consisted of nurses' written records, a brief survey among all nurses and individual interviews with eight nurses. Data analysis encompassed numerical analyses as well as descriptive content analysis. Findings Camera‐assisted observation was implemented by 44 patients from 60-95 years old, for 6 months. The practicality was enhanced by equipment that was easy to operate but the nurses were hampered by carrying the institutional mobile phone while caring for other patients. The intervention's acceptability depended on its potential for improved patient safety and the ability to adjust nursing care to meet the patients' needs as this could enhance feelings of confidence and control.